Russia and the World: 2016 IMEMO Forecast. Issue 2 (September 2015) - Dynkin, A.; Baranovsky, V.; Kobrinskaya, I.; Machavariany, G.; Afontsev, S.; Kuznetsov, A.; Voytolovsky, F.; Shvydko, V.; Utkin, S.; Mikheev, V.; Lukonin, S.; Federovsky, A.; et al.
This forecast examines the major trends in Russia's relations with the world and in the Russian view of the world in 2016. The forecast looks firstly at Russia's role in the world in the context of the extant and emergent state of geopolitics. In a confused international environment, caught between the multiple, discordant and disorderly games of checkers of the present and the emerging design of a new grand chessboard for international relations, Russia and the West have been forced into cooperation. While far from easy and far from guaranteed to work – or last – this situation does offer the possibility of overcoming divides to pursue mutual interests. These interests become particularly apparent in the context of increased shared threats and the need to act jointly against them, the uncertainties created by rising powers, and the difficulties that Russia finds itself in. The key role of new mega-regional trade agreements in this emerging great game is also emphasised in the subsequent sections of the forecast, which deal, respectively, with foreign policy and political economy. The foreign policy analysis sees the US in flux in a presidential election year, and the EU caught at the crossroads of its own failure to capitalise on integration and a migration crisis of unprecedented proportions. Meanwhile, foreign policy in the post-Soviet space is characterised more by stasis than by substantial change, with frozen conflicts and stagnant reforms in Ukraine and limited room for manoeuvre for other players the order of the day. The Russian involvement in the Middle East, however, is anything but stagnant, with the military operations in Syria having dramatic effects in both the situation in Syria and global and regional geopolitics. The sustainability of this quest for influence, however, is questioned by the attitude of other players, but also by Russia's own internal weaknesses, notably its serious and deepening economic crisis.